Diálogos institucionais no Plano subnacional: o Tribunal de Justiça do estado de Pernambuco e a Assembleia Legislativa do Estado de Pernambuco. - Lima, Ricardo Freire Tavares de Andrade (2021)
The main objective of this research is to analyze institutional the dialogues at the subnational level, their limits and possibilities, considering the performance of the Judiciary and the Legislative in democratic horizon. The growing judicial protagonism has taken the judge to the role of maximized actor in contemporary (neo)constitutionalism. In this context, the Judiciary has shown a prominent role in recent decades with the extension of its functions beyond the interpretation and safeguard of the Constitution in the propagation of constitutional precepts. In the context of the current judicial protagonism, the burden of legitimacy to be sought by judicial decisions is increased. In this tuning fork, institutional dialogues between powers, more specifically between the Judiciary and the Legislative, represent a perspective of protection to constitutional precepts, considering the evident need to transform the role of the Judiciary and the revaluation of the Legislative. For the development of this work, the Court of Justice of Pernambuco and the Legislative Assembly of Pernambuco were chosen specific research object, in relation to the last legislature, corresponding to the period between 2015 and 2018. It seeks to understand the structure of institutional dialogues at the subnational level based on case studies, using bibliographical and jurisprudential research as methods of data collection.